2022
DOI: 10.1155/2022/7634951
|View full text |Cite
|
Sign up to set email alerts
|

Study on Rheological Characteristics of Uncemented Coal Gangue-Fly Ash Backfill (UCGFB) Slurry Based on Fractal Theory

Abstract: In order to explore the influence of gradation and concentration on the rheological parameters of uncemented coal gangue-fly ash backfill (UCGFB) slurry, based on the fractal theory, the particle size distribution of the mixture of coal gangue and fly ash under different mixing ratios are analyzed in this paper. On this basis, the influence of gradation and concentration on rheological parameters of UCGFB slurry are studied and a numerical simulation of slurry transportation is also carried out. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Therefore, paste-filling technology has become a hot spot of research and application in recent years: Zhang Qinli and Wang Xinmin, et al studied the movement form of the filling paste in the pipeline gravity conveying system and the settlement law of solid particles of filling aggregate and theoretically analyzed the feasibility of pipeline gravity conveying with coal gangue as the major aggregate [4]. Yang Jiaqiang and Zhou Yao, et al studied the effect of different particle sizes and water-gangue ratios on the rheological properties of coal gangue paste by testing the rheological properties, fluidity and flow time of coal gangue paste and discussed the change rules of the rheological parameters, fluidity and flow time [5][6][7]. Zhu Lei and Huang Yucheng, et al have carried out research and an engineering application for the pipe-filling technology of the paste made of coal gangue as an aggregate [8][9][10][11][12], conducted simulation and experimental research on the flow and diffusion laws of the gangue-filling paste in the caving zone above the underground work and discussed the underground treatment and fluidized filling technology in the inbreak area [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, paste-filling technology has become a hot spot of research and application in recent years: Zhang Qinli and Wang Xinmin, et al studied the movement form of the filling paste in the pipeline gravity conveying system and the settlement law of solid particles of filling aggregate and theoretically analyzed the feasibility of pipeline gravity conveying with coal gangue as the major aggregate [4]. Yang Jiaqiang and Zhou Yao, et al studied the effect of different particle sizes and water-gangue ratios on the rheological properties of coal gangue paste by testing the rheological properties, fluidity and flow time of coal gangue paste and discussed the change rules of the rheological parameters, fluidity and flow time [5][6][7]. Zhu Lei and Huang Yucheng, et al have carried out research and an engineering application for the pipe-filling technology of the paste made of coal gangue as an aggregate [8][9][10][11][12], conducted simulation and experimental research on the flow and diffusion laws of the gangue-filling paste in the caving zone above the underground work and discussed the underground treatment and fluidized filling technology in the inbreak area [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [21] studied the effects of gangue mass fraction, particle gradation and standing time on the rheological properties of gangue lling slurry, and con rmed that the characteristics of coal gangue slurry belong to Bingham uid. Based on fractal theory, Jin et al [22] analyzed the particle size distribution of coal gangue-y ash mixture under different mixing ratios, and studied the effects of gradation and concentration on the rheological parameters of coal gangue-y ash slurry. Wang et al [23] obtained the spatial distribution expression of viscosity decay rate considering the in uence of water-cement ratio through a one-dimensional visual grouting test, and derived the Bingham uid column permeability grouting theoretical formula considering the spatial decay of viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al 22 studied the effects of gangue mass fraction, particle gradation and standing time on the rheological properties of gangue filling slurry, and confirmed that the characteristics of coal gangue slurry belong to Bingham fluid. Jin et al 23 , 24 analyzed the particle size distribution of coal gangue-fly ash mixture under different mixing ratios, and studied the effects of gradation and concentration on the rheological parameters of coal gangue-fly ash slurry. Wang et al 25 obtained the spatial distribution expression of viscosity decay rate considering the influence of water-cement ratio through a one-dimensional visual grouting test, and derived the Bingham fluid column permeability grouting theoretical formula considering the spatial decay of viscosity.…”
Section: Introductionmentioning
confidence: 99%